"Evaluating Celebrity Endorsement's Impact on Brand love through Brand Image in the Context of Industry Diversity: Food and Beverage and Telecommunications in Egyptian Market" "تقييم تأثير تأييد المشاهير على حب العلامة التجارية من خلال صورة العلامة التجارية في سياق تنوع الصناعة: الأغذية والمشروبات والاتصالات في السوق المصري" - نرمين السعدني; مروة حسام; سيد شرف (Maǧallaẗ Al-Buḥūṯ Al-Mālīyyaẗ wa Al-Tiğāriyyaẗ)
This study aims to explore the impact of celebrity endorsement in social media advertisements for food, beverages, and telecommunications on brand love through brand image. Structural Equation Modeling (SEM) was used to analyze the data collected from a convenience sample of 399 students at Cairo and Port Said universities. The results indicated the vital role of brand image as a mediating variable in the relationship between celebrity endorsement (credibility, attractiveness, and expertise) and brand love. Additionally, a favorable impact was observed for brand image on brand love.تهدف هذه الدراسة إلى اكتشاف أثر تأييد الشخصية الشهيرة فى إعلانات الأغذية والمشروبات والاتصالات في مصر على حب العلامة التجارية من خلال صورة العلامة التجارية. تم استخدام نمذجة المعادلات الهيكلية (SEM) لتحليل البيانات التي تم جمعها من عينة ميسرة من 399 طالبًا في جامعتي القاهرة وبورسعيد. أظهرت النتائج الدور الحيوي لصورة العلامة التجارية كمتغير وسيط في العلاقة بين دعم الشخصية الشهيرة (المصداقية، والجاذبية، والخبرة) وحب العلامة التجارية. بالإضافة إلى ذلك، لوحظ تأثير إيجابي لصورة العلامة التجارية على حب العلامة التجارية.